A Study on Prediction of Student Academic Performance based on Expert Systems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years , research evolution in domain of education focus on analytics and which provides insights on students academic performance. The tremendous growth of instructional institutions’ electronic information provides the chance to extract info which will be wont to predict students’ overall success, predict students’ dropout rate, appraise the performance of academics and instructors, improve the learning material in step with students’ desires, and far a lot of. This paper aims to review the latest trends in predicting students’ performance in educational activity. we explain the measures of determinant educational success and highlight the strengths and weaknesses of the foremost common data processing (DM) tools and strategies used today. Moreover, we offer a fashionable literature review of the EDM work that has been revealed during the past years with target the prediction of educational performance in educational activity. we tend to analyze the foremost normally used options and strategies in predicting educational accomplishment, and highlight the advantages of the principally used DM tools in EDM. The results of this paper might assist researchers who  are working to hold out EDM solutions within the domain of education as we tend to highlight the type of options that the previous researches found to possess important impact on the prediction, likewise because the edges and downsides of the DM strategies and tools used for predicting educational outcomes.